Bicarbonate Induced Redox Proteome Changes in Arabidopsis Suspension Cells - Yin, Zepeng; Balmant, Kelly; Geng, Sisi; Zhu, Ning; Zhang, Tong; Dufresne, Craig; Dai, Shaojun; Chen, Sixue (Frontiers in Plant Science, 2017)
Climate change as a result of increasing atmospheric CO2 affects plant growth and productivity. CO2 is not only a carbon donor for photosynthesis but also an environmental signal that can perturb cellular redox homeostasis and lead to modifications of redox-sensitive proteins. Although redox regulation of protein functions has emerged as an important mechanism in several biological processes, protein redox modifications and how they function in plant CO2 response remain unclear. Here a new iodoTMTRAQ proteomics technology was employed to analyze changes in protein redox modifications in Arabidopsis thaliana suspension cells in response to bicarbonate (mimic of elevated CO2) in a time-course study. A total of 47 potential redox-regulated proteins were identified with functions in carbohydrate and energy metabolism, transport, ROS scavenging, cell structure modulation and protein turnover. This inventory of previously unknown redox responsive proteins in Arabidopsis bicarbonate responses lays a foundation for future research toward understanding the molecular mechanisms underlying plant CO2 responses.